Distribution and clinical significance of peripheral blood lymphocyte PD-1 and PD-L1 in non-Hodgkin lymphoma: a retrospective study in Chinese patients - Liu, Lu; Wang, Lei; Wang, Wei; Wang, Yansu; Wang, Yanrong; Xu, Na; Li, Na; Liu, Haifeng (Frontiers in Oncology, 2026)
BackgroundProgrammed death-1 (PD-1) and its ligand PD-L1 play critical roles in immune checkpoint regulation. This study investigated the relationship between PD-1 and PD-L1 expression on peripheral blood lymphocytes and Non- Hodgkin Lymphoma progression.MethodsThis retrospective study included patients diagnosed with Non- Hodgkin Lymphoma at Jilin Cancer Hospital between October 2013 and May 2017. PD-1 and PD-L1 expression on CD4+ and CD8+ T cells was analyzed using flow cytometry.ResultsA total of 125 non- Hodgkin Lymphoma patients (65 males and 60 females; median age, 57 years; range, 14–86 years) were included. PD-1 and PD-L1 expression on CD8+ T cells was significantly higher in patients with elevated lactate dehydrogenase (LDH) (>245 U/L) than in those with normal LDH (PD-1: 16.46% vs. 12.68%, P = 0.005; PD-L1: 9.96% vs. 7.90%, P = 0.043). PD-1 expression on CD8+ T cells was also higher in patients with bone marrow involvement compared with those without (17.62% vs. 14.56%, P = 0.039). Furthermore, PD-L1 expression on both CD4+ and CD8+ T cells was significantly lower in patients who achieved complete response (CR) compared with those with non-CR (CD4+: 11.14% vs. 18.61%, P<0.001; CD8+: 7.19% vs. 10.60%, P = 0.032). Notably, a decrease in CD4+ PD-1 levels after treatment showed a strong trend towards improved overall survival compared with cases showing increased levels (median survival not reached in the decreased group vs. 41.77 months in the increased group, P = 0.066).ConclusionPeripheral blood lymphocyte PD-1 and PD-L1 expression are associated with LDH levels, bone marrow involvement, and treatment response. A reduction in CD4+ PD-1 levels after treatment is associated with a trend towards improved overall survival.